The crown - Cass, Kiera (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2016)
Twenty years have passed since America Singer and Prince Maxon fell in love, and their daughter is the first princess to hold a Selection of her own.
Keywords: Princesses -- Juvenile fiction; Social classes -- Juvenile fiction; Contests -- Juvenile fiction; Marriage -- Juvenile fiction; Young adult fiction